Psychological Approaches in the Love Curriculum: A Humanistic Education Perspective - Cucum Novianti; Jajat Darojat (Asesment : Journal Of Counseling Guidance, 2026)
Background : This research is motivated by the problem of contemporary education, which tends to emphasize cognitive aspects and academic achievement while neglecting students' emotional, social, and human dimensions. This condition highlights the need for an educational paradigm that promotes holistic human development. Objectives : To analyze the psychological approach in the love curriculum from a humanistic education perspective. Method : This study employed a qualitative approach using a library research design. Data sources were obtained from books, scientific journals, research findings, and academic documents related to educational psychology, humanistic education, humanistic pedagogy, and the love curriculum. Data were collected through documentation studies and analyzed using content analysis, including data reduction, data presentation, and conclusion drawing. Finding and Implication : The findings indicate that the love curriculum represents an affective educational paradigm that emphasizes compassion, empathy, respect for human beings, and humanistic interpersonal relationships as the foundation of the learning process. The psychological approach within the love curriculum contributes significantly to enhancing learning motivation, emotional intelligence, character development, and dialogical relationships between teachers and students. Its implementation can be realized through participatory learning, a humanistic school culture, and pedagogical approaches that position students as active subjects of education. These findings imply that the love curriculum can serve as an effective strategy for fostering more meaningful and holistic educational experiences. Conclusion : The love curriculum is relevant as a humanistic educational paradigm that promotes empathetic, inclusive, and student-centered learning while supporting the comprehensive development of human potential.